A Directory of resource persons in Western Visayas a preliminary listing - Funtecha, Henry F. (Center for West Visayan Studies, U.P. in the Visayas, 1990)
This directory is the preliminary listing of resource persons in Western Visayas which specifically serves as a medium for access to persons who can be of valuable assistance in research projects, conferences, training programs, cultural presentations and the like prior to the year 1990. It surveys significant persons who contribute to the preservation, study and propagation of Western Visayan culture and history.